Analisis Triple Bottom Line Warung Kopi Dalam Menghadapi Coffee Shop Di Kawasan Brotonegoro Gresik - Fauziyah, Atikotul; Handayani, Anita (Jurnal Mahasiswa Manajemen, 2021)
Background - Changes in the lifestyle of young people who mostly prefer to hang out at coffee shops, so that the interest in coffee shops decreases. but contrary to the condition of the coffee shop in the Brotonegoro Gresik area which still survives to obtain optimal profit. Objective - This study aims to analyze the triple bottom line of coffee shops in the Brotonegoro Gresik area to deal with modern coffee shops in obtaining optimal profit. Design/Methodology/Approach - The technique used in this research is purposive sampling with structured interviews and unstructured interviews (free) Findings - The results of this study found that coffee shops pay attention to the environment (planet) by paying attention to the cleanliness of the coffee shop premises, the facilities provided, and paying attention to the layout (layout) of food and beverages being sold. Coffee shops pay attention to service (people), namely by maintaining ethics, paying attention to appearance, and maintaining quality. Profit (profit) as the fulfillment of the necessities of life and business continuity for coffee shop owners in the Brotonegoro Gresik area. Research implications - The results of this research can be used as a reference for coffee shop owners to provide added value and develop their business. Research limitations - Research conducted by researchers still has limitations, namely researchers have not explored service quality more deeply, so that the information obtained by researchers in the form of service quality is only based on the dimensions of reliability, certainty and empathy.